Association of prenatal exposure to gestational diabetes with offspring body composition and regional body fat distribution. Issue 2 (13th December 2017) - Kearney, M.; Perron, J.; Marc, I.; Weisnagel, S. J.; Tchernof, A.; Robitaille, J.
Summary: The aim of this cohort study was to compare body composition and regional body fat distribution between children exposed (GDM+) or unexposed (GDM−) in utero to gestational diabetes mellitus (GDM) and to investigate the association with the glycaemic and the insulin profile. Data from 56 GDM+ and 30 GDM− were analysed. Height, weight and waist circumference were measured. Total and regional body composition was measured by dual‐energy X‐ray absorptiometry. Insulin, glucose and HbA1c were obtained from a fasting plasma sample, and the HOMA‐IR index was calculated.anova was performed to compare adiposity measures between GDM+ and GDM−. Associations between the glycaemic and insulin profile and adiposity measures were studied using partial Pearson correlations. Mean age was 6.6 ± 2.3 years. Waist circumference, fat mass percentage, android fat mass, android fat mass percentage and android‐to‐gynoid fat mass ratio were higher among GDM+, and lean mass percentage was lower ( P < 0.05). Among GDM+ children, body mass index (BMI) z score, waist circumference, fat mass percentage, android fat mass percentage and android‐to‐gynoid fat mass ratio were all positively correlated with HbA1C ( r = 0.32–0.43, P < 0.05). Prenatal exposure to GDM is associated with increased total and abdominal adiposity. This increased adiposity observed among GDM+ children is associated with an altered glycaemic profile. This study is registered in the ClinicalTrials.gov registry (NCT01340924).